2010
DOI: 10.1186/1472-6963-10-159
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' use of the 5As in counseling obese patients: is the quality of counseling associated with patients' motivation and intention to lose weight?

Abstract: BackgroundPhysicians are encouraged to counsel obese patients to lose weight, but studies measuring the quality of physicians' counseling are rare. We sought to describe the quality of physicians' obesity counseling and to determine associations between the quality of counseling and obese patients' motivation and intentions to lose weight, key predictors of behavior change.MethodsWe conducted post-visit surveys with obese patients to assess physician's use of 5As counseling techniques and the overall patient-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
118
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 39 publications
(39 reference statements)
1
118
0
2
Order By: Relevance
“…Our finding that few individuals with obesity make it to the end of the cascade suggests that there is significant unmet need for obesity care at the population level. Engaging with this last step is essential to gaining access to managed, effective care and can result in a myriad of treatment outcomes, including behavioral modification, pharmacotherapy, bariatric surgery, and/or referral to another care provider 17, 18, 19, 20, 21. Our findings thus highlight the need for physicians to engage in conversation about obesity treatment at routine clinical visits, even when patients are not seeking obesity care.…”
Section: Discussionmentioning
confidence: 83%
“…Our finding that few individuals with obesity make it to the end of the cascade suggests that there is significant unmet need for obesity care at the population level. Engaging with this last step is essential to gaining access to managed, effective care and can result in a myriad of treatment outcomes, including behavioral modification, pharmacotherapy, bariatric surgery, and/or referral to another care provider 17, 18, 19, 20, 21. Our findings thus highlight the need for physicians to engage in conversation about obesity treatment at routine clinical visits, even when patients are not seeking obesity care.…”
Section: Discussionmentioning
confidence: 83%
“…Physician use of a patient-centered approach has been shown to be associated with patient intention to exercise. 20 Exploring ambivalence is an important feature of patient-centered physical activity discussions. Patient-centered communication skills may be particularly helpful when physical activity is discussed in the context of weight management, as it is common for patients and physicians to have discrepant perceptions regarding weight.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work examining the 5As for smoking found that patients contributed to accomplishing some of the 5As 17,20 ; therefore, the coding scheme for the 5As for physical activity incorporated patient contribution to accomplishing the 5As. Drawing from a sample of 135 offi ce visits with audio-recorded discussions of physical activity, we used the preliminary template to code an initial sample of 10 discussions.…”
Section: Methodsmentioning
confidence: 99%
“…46 Use of the 5 A's is associated with change in health behaviors across diverse populations and health behaviors. [47][48][49] Because the 5 A's model covers the key elements of selfmanagement support, it presents a guiding conceptual framework for evaluating and implementing behavioral change counseling interventions in chronic disease management (Clinical Scenario 3). 50 Thus, this framework could be easily adapted to facilitate a person-centered approach to address medication adherence.…”
Section: Motivational Interviewing and Counselingmentioning
confidence: 99%